Comparison of the effects of different percentages of soy protein in the diet on patients with type 2 diabetic nephropathy: systematic reviews and network meta-analysis - Sun, Jun; Wei, Yu; Miao, Runyu; Zhang, Xiangyuan; Zhang, Boxun; Zhang, Lili; Zhao, Linhua (Frontiers in Nutrition, 2023)
Background Dietary soy protein (SP) is a potential intervention for protecting the kidney and improving glucose and lipid metabolism. However, whether this effect is related to the percentage of SP intake remains unclear. Objective: This study aimed to review and analyze the results of randomized clinical trials (RCTs) in patients with type 2 diabetic nephropathy (T2DN) who received diets with different percentages of SP. Methods The databases: PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, China National Knowledge Infrastructure (CNKI), Chinese BioMedical Literature Database(CBM), WanFang, Weipu (VIP), and ClinicalTrials.gov were searched until February 2023, for RCTs on T2DN and SP. Results: A total of six studies comprising 116 participants were included. The interventions were classified as 0%SP,35%SP, and 100%SP. To improve serum creatinine (Scr), blood urea nitrogen (BUN), 24-hour urine total protein (24hUTP), and glomerular filtration rate (GFR), a 35% SP diet was the most effective, as compared to a 0% SP diet, which showed a mean difference of -154.00 (95% confidence interval: -266.69, -41.31) for 24hUTP. Although it had significant benefits for 24hUTP, great heterogeneity was observed. To improve the glycolipid metabolism-related markers such as cholesterol (CHO), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), fasting blood glucose (FPG), and weight, the 35% SP diet demonstrated superior efficacy compared to the 0% SP diet. Specifically, the mean difference for CHO was -0.55 (95% confidence interval: -1.08, -0.03), and for LDL-C, it was -17.71 (95% confidence interval: -39.67, -4.24). The other indicators were not statistically significant. Most studies had concerns regarding the risk of bias.The findings of this study demonstrated that both 35% and 100% SP diets were more effective than a diet with no SP in improving renal function and glucolipid metabolism in patients with T2DN. As a result, a diet incorporating 35% SP may be the optimal choice for individuals with T2DN.